IMPROVING STUDENT ACHIEVEMENT IN THE SUBJECTS OF ISLAMIC RELIGIOUS EDUCATION - Ahmad Yasa; Imam Asrofi (Jurnal Pendidikan Islam, 2014)
The purpose of this study was (1) to know a difference between student learning outcomes of low and high sub groups with learning to use the media worksheets in the subjects of Islamic Religious Education (Pendidikan Agama Islam); and (2) to know the obstacles in the implementation of learning by using the worksheets on the subject. The subjects study were three Open Junior High Schools, Bandung, namely Open Junior High School 8 Bandung, Open Junior High School 27 Bandung, and Open Junior High School 36 Bandung. The hypothesis tested the increase in student achievement in the subjects of Islamic Religious Education after a learning process using worksheets. This study was a quasi-experimental study. The design used in this study is a pre-test post-test one group design. The results show that learning outcomes after the use of worksheets has no significant difference. Then the t-test Test Final Problem Description pretest and posttest seen that the value of significance (sig.2-tailed) with the t-test is 0.007. Since the significance value less than 0.05 then the decision-making criteria, H0 rejected. This shows that learning outcomes after the use of worksheets has significant difference. Using the analysis, the results showed that the use of worksheets in the learning process could improve the learning outcomes of students in the subjects of Islamic Religious Education in junior high school in Bandung.